EFFECTS OF NATURAL COLORANTS AND PULSED ELECTRIC FIELD TECHNOLOGY ON QUALITY PARAMETERS OF NITRITE-FREE BACON - Molina, Jan Roland; Frías Celayeta, Jesús María; Bolton, Declan; Botinestean, Cristina (Food and Feed Research, 2024)
The replacement of nitrites in cured meat products, such as bacon chops, presents challenges in maintaining the characteristic pink colour and other quality attributes. This study evaluates the effectiveness of natural colorants: betanin, red yeast (Monascus) rice extract, and roselle (Hibiscus sabdariffa) extract, as alternatives to nitrites for colour enhancement in nitrite-free bacon. Pulsed electric field (PEF) pre-treatment was applied to samples prior to immersing in brine with colorant. Bacon loins were treated with brines containing different concentrations of these colorants, then vacuum packaged, tumbled, and stored at 4°C until further testing. Instrumental colour parameters (L*, a*, b*, hue angle, chroma, and cured colour ratio) were measured for both uncooked and cooked samples. Results showed that uncooked bacon treated with 0.05% betanin exhibited similar redness (a*) and cured colour ratios to nitrite-treated controls, indicating that betanin has potential as a feasible colorant. Red yeast rice extract at 0.10% also enhanced redness but increased yellowness (b*), affecting the overall colour. Upon cooking, a* values of colorant-treated bacon were comparable with the nitrite-treated sample. However, they all displayed significantly (P
Keywords: nitrite-free; meat products; natural colorants